Excess NF-κB Induces Ectopic Odontogenesis in Embryonic Incisor Epithelium - Blackburn, J. (J Dent Res, 2014)
Nuclear factor kappa B (NF-κB) signaling plays critical roles in many physiological and pathological processes, including regulating organogenesis. Down-regulation of NF-κB signaling during development results in hypohidrotic ectodermal dysplasia. The roles of NF-κB signaling in tooth development, however, are not fully understood. We examined mice overexpressing IKKβ, an essential component of the NF-κB pathway, under keratin 5 promoter (K5-Ikkβ). K5-Ikkβ mice showed supernumerary incisors whose formation was accompanied by up-regulation of canonical Wnt signaling. Apoptosis that is normally observed in wild-type incisor epithelium was reduced in K5-Ikkβ mice. The supernumerary incisors in K5-Ikkβ mice were found to phenocopy extra incisors in mice with mutations of Wnt inhibitor, Wise. Excess NF-κB activity thus induces an ectopic odontogenesis program that is usually suppressed under physiological conditions.